Penegakan Hukum Terhadap Angkutan Umum Yang Tidak Memenuhi Persyaratan Teknis Dan Laik Jalan Di Suku Dinas Perhubungan Kota Administrasi Jakarta Utara - Hilda Adinta Wulandari (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Law enforcement against public transportation that does not meet the technical and roadworthy requirements by the North Jakarta City Transportation Office is to take action in the form of tickets by providing ticket stamps by following the trial to the local District Court and the obstacles faced by the North Jakarta City Transportation Office, namely the lack of innovative power, the existence of several irresponsible individuals by making illegal levies (extortion) to a number of drivers and/or business owners of public transportation, especially in administrative arrangements and so on.